2020
DOI: 10.1136/bmjos-2019-100040
|View full text |Cite
|
Sign up to set email alerts
|

Crocodylus porosus: a potential source of anticancer moleculesCrocodylus porosus: a potential source of anticancer molecules

Abstract: BackgroundCancer remains a global threat resulting in significant morbidity and mortality despite advances in therapeutic interventions, suggesting urgency for identification of anticancer agents. Crocodiles thrive in polluted habitat, feed on germ-infested meat, are exposed to carcinogenic heavy metals, are the very few species to survive the catastrophic Cretaceous–Paleogene extinction event, yet have a prolonged lifespan and rarely been reported to develop cancer. Therefore, we hypothesised that animals liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 70 publications
0
20
0
Order By: Relevance
“…Moreover, this study elucidated the differential gene analysis of cancer cells incubated with crocodile sera. These analyses revealed that 51 genes in breast cancer cells, 14 genes in treated cervical cancer cells and 2 genes in prostate cancer cell lines were differentially expressed in comparison to untreated cells and the study revealed that these genes were typically involved in cellular communication, DNA growth and repair, respiration and others ( Jeyamogan et al., 2020 ). Nonetheless, the precise genetic mechanisms for these anti-cancer effects remain to be determined, and further research to determine the connection with the gut microbiome and its’ metabolites are currently underway ( Khan et al., 2021 ).…”
Section: Crocodile Anti-cancer Properties and Ageingmentioning
confidence: 99%
See 4 more Smart Citations
“…Moreover, this study elucidated the differential gene analysis of cancer cells incubated with crocodile sera. These analyses revealed that 51 genes in breast cancer cells, 14 genes in treated cervical cancer cells and 2 genes in prostate cancer cell lines were differentially expressed in comparison to untreated cells and the study revealed that these genes were typically involved in cellular communication, DNA growth and repair, respiration and others ( Jeyamogan et al., 2020 ). Nonetheless, the precise genetic mechanisms for these anti-cancer effects remain to be determined, and further research to determine the connection with the gut microbiome and its’ metabolites are currently underway ( Khan et al., 2021 ).…”
Section: Crocodile Anti-cancer Properties and Ageingmentioning
confidence: 99%
“…This was based on the longevity of crocodiles, with some living up to 100 years and our visits to numerous crocodile farms and sanctuaries as well as personal communication with veterinarians and zoologists, who indicated the absence of cancer cases in these species ( Jeyamogan et al., 2017 ). In this regard a study was conducted, whereby the anti-cancer effects of crocodile sera and various organ lysates were investigated against cervical, breast and prostate cancer cells ( Jeyamogan et al., 2020 ). Crocodile serum depicted potent growth inhibitory effects as well as cytotoxic effects against the cancer cells investigated.…”
Section: Crocodile Anti-cancer Properties and Ageingmentioning
confidence: 99%
See 3 more Smart Citations